Tinjauan Yuridis Mekanisme Penyelesaian Sengketa Hasil Pemilu Presiden Oleh Mahkamah Konstitusi - Putri, Amanda Fitriani Eka; Rasji, Rasji; Puspita, Salsabillah Ayu (Peneliti.net, 2024)
Elections serve as a means of implementing the sovereignty of the people, carried out directly, universally, freely, secretly, honestly, and fairly within the Unitary State of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Elections are a manifestation of democracy and an important aspect to be carried out democratically. This research aims to analyze the mechanism for resolving and handling disputes over the results of the Presidential Election by the Constitutional Court according to applicable law. In this study, a normative juridical research method is used with data collection through document studies. The data sources obtained are secondary data, such as journals, articles, papers, news, and laws. This research concludes that the resolution of election disputes can be resolved through institutions, one of which is the Constitutional Court (CC). The CC's decisions have legal force. This research provides a clearer understanding of the CC's decisions and the resolution of Presidential Election disputes through the CC. It is expected to enrich the knowledge of the public, especially for students.